A Study of Causes and Clinicopathological Changes of Patients Presented with Hoarseness of Voice in the ENT Department of Hilla Teaching General Hospital, Babylon, Iraq - Maytham Lafta Kreem Witwit (Medical Journal of Babylon, 2024)
Background: Hoarseness of voice (HOV) is defined as abnormal changes in the quality of voice. It may be caused by many diseases related to the upper aerodigestive tract system. Proper knowledge about the causes and clinicopathological changes leading to HOV is very important for the early detection and treatment of the causative pathology. Objective: To investigate the causes, incidence, age, occupation, and sex predilection for HOV. Materials and Methods: This prospective study was carried out on 200 patients referred to the Eyes, Nose, and Throat (ENT) Department of Hilla Teaching General Hospital, Babylon, Iraq, from September 2017 to September 2019 complaining of HOV for more than 10 days. The ENT examination was conducted using a fiberoptic flexible laryngoscope. Radiological examination by plain X-ray of the neck and chest, computed tomography scans of the head, neck, and chest, and a direct laryngoscopy exam. Under general anesthesia, and biopsy is taken from suspected pathology (if needed). Results: Out of 200 patients, the age group between 31 and 40 years was most commonly seen. Laborers occupation 30% farmers 35% were the major groups affected. Smoking habits were found in 40% of patients with HOV. The most common causes of HOV were acute and chronic laryngitis, including acute viral laryngitis, acute voice abuse, laryngeal trauma after thyroid surgery, vocal cord (VC) nodules, laryngeal polyps, and laryngeal edema. The second most frequent causes are neoplastic growths in the larynx (mostly supraglottic) and hypopharynx. The least frequent causes of HOV are seen due to congenital pathologies such as laryngomalacia and congenital VC palsy. Conclusion: Proper and detailed history, good ENT examination, and the investigation of patients with HOV are important factors in the early detection and treatment of causative pathology.